Atrial Fibrillation Burden Detected by Dual-Chamber Pacemakers as a Predictor for Cardiac Outcomes: A Retrospective Single-Center Cohort Study - Chu, Song-Yun; Jiang, Jie; Wang, Yu-Ling; Sheng, Qin-Hui; Zhou, Jing; Ding, Yan-Sheng (Frontiers in Cardiovascular Medicine, 2021)
Background: Atrial fibrillation (AF) might lead to adverse cardiac consequences. The association between AF burden and the cardiac prognosis is unknown. Methods and Results: This retrospective cohort study enrolled 204 patients (117 males; age 74.5±11.5 years) who underwent dual-chamber pacemaker implantation in our center from October 2003 to May 2017. During a median follow-up of 66.5 months, AF could be detected in 153 (75%) of 204 pacemaker patients. Primary endpoint events (composite cardiac re-admission, stroke or systemic embolism, and all-cause death) occurred in 83 cases (40.7%). In Logistic regression analysis, AF detection was associated with increased risks of composite endpoints [Odds ratio(OR)=2.9, 95% Confidence interval (CI): 1.3-6.2, p=0.007] and the hazard was mainly driven by increased cardiac re-admission (OR=2.2, 95% CI: 1.1-4.7, p=0.034). No significantly elevated risk for new-onset stroke, systemic embolism, or deaths was found in patients with AF detected than those without AF recorded. AF duration grade of more than 6 minutes suggested progressively increased composite endpoints (OR=1.8, 95% CI: 1.2-2.7, p for trend=0.005), cardiac re-admission (OR=1.8, 95% CI: 1.2-2.7, p for trend=0.005), especially heart failure or acute coronary syndrome-associated re-admission (OR=1.8, 95% CI: 1.2-2.9, p for trend=0.010) than those with shorter (less than 6 minutes) or no AF episodes. Kaplan-Meier analyses and Cox regression also suggested that episodes of AF more than 6 minutes predicted future cardiac events. Conclusions: AF detected by pacemakers were common. Higher AF burden predicted more adverse cardiac outcomes and might suggest the intervention of rhythm control in these populations.